2010
DOI: 10.1007/s10344-009-0358-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary shifts in two vultures after the demise of supplementary feeding stations: consequences of the EU sanitary legislation

Abstract: Among vertebrates, specialization in scavenging has appeared only in "true" Gyps vultures, which usually base their diet almost exclusively on carcasses of medium and large-sized mammals, whereas all other scavengers rely on broader ranges of prey. The availability of food for scavengers in Western Europe has not been limited during recent decades permitting the existence and growth of huge vulture populations. From 2000 onwards, however, EU sanitary legislation has progressively limited the abandonment of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 36 publications
2
92
1
1
Order By: Relevance
“…The fact that this study was performed at fixed feeding locations could enhance this effect and partially bias the conclusions with regards to unmanaged situations (Monsarrat et al, 2013). In this sense, the most specialist and territorial vultures balance this negative situation and optimize carrion ingestion with improved detection capabilities of small carcasses from a wider range of wildlife species randomly distributed in the field (Ceballos and Donázar, 1990;Margalida et al, 2009;Donázar et al, 2010).…”
Section: Interspecific Relationshipsmentioning
confidence: 95%
See 1 more Smart Citation
“…The fact that this study was performed at fixed feeding locations could enhance this effect and partially bias the conclusions with regards to unmanaged situations (Monsarrat et al, 2013). In this sense, the most specialist and territorial vultures balance this negative situation and optimize carrion ingestion with improved detection capabilities of small carcasses from a wider range of wildlife species randomly distributed in the field (Ceballos and Donázar, 1990;Margalida et al, 2009;Donázar et al, 2010).…”
Section: Interspecific Relationshipsmentioning
confidence: 95%
“…Finally, the Egyptian vulture optimized intake efficiency when the input consisted of remains formed by meat, entrails and bones. Due to its soft texture, this type of input would lead to small pieces and scraps not initially hoarded by the griffon vulture (Ceballos and Donázar, 1990;Donázar et al, 2010).…”
Section: Tablementioning
confidence: 98%
“…As a result of these changes, wolf population in Galicia has become highly dependent on roe deer and wild pony population. Previous studies have indicated that these same sanitary measures have affected avian scavenger populations and ecology (Camiña and Montelío 2006;Donázar et al 2010;Margalida et al 2010;Camiña and Yosef 2012).…”
Section: Resultsmentioning
confidence: 97%
“…The changes in the livestock carcass disposal systems from 2000 onwards first opened the debate on how these new regulations might affect the ecology and conservation of endangered populations of scavenging birds (Tella 2001). As a consequence, several studies were conducted on the impact of those regulations on vultures (Camiña and Montelío 2006;Donázar et al 2010;Camiña and Yosef 2012). Wolves were also considered potentially vulnerable to those regulatory changes which restricted carrion availability (Barrientos et al 2005;Blanco and Cortés 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Species managed by supplementary feeding include: the California Condor ( Gymnogyps californianus) in Western North America; the King Vulture ( Sacorramphus papa) in Belize; and the Cape Vulture ( Gyps coprotheres) and bearded vulture in Southern Africa (Wilbur and Jackson 1983;Houston 1987;Brown 1990;Mundy et al 1992). In Eurasia, vulture restaurants have mainly targeted populations of bearded, Egyptian, griffon, and cinereous vultures (Donázar 1993;Donázar et al 2009aDonázar et al , 2010Cortés-Avizanda et al 2010;Fig. 5.4).…”
Section: Vulture Restaurants and The Loss Of A Pulsed Resourcementioning
confidence: 99%